Simple Antivirus Scanner: A Signature-Based Malware Detection System Using Delphi - Alin, Antonov (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The Simple Antivirus Scanner was developed as an instructional model to demonstrate the core mechanisms of signature-based malware detection. Implemented using Delphi, the system integrates MD5 hashing, database-driven signature comparison, and asynchronous scanning through the TBackgroundWorker component, providing both functionality and responsiveness in a Windows environment. The project’s architecture includes recursive file traversal, efficient hash computation, and a structured virus definition database that enables accurate identification of known malware. The inclusion of a harmless test virus allows for safe experimentation and validation of the detection process, reinforcing user understanding of hash-based recognition. Results show that the system performs effectively in detecting catalogued threats, offering a predictable and transparent learning experience. However, it lacks the capabilities of modern antivirus systems such as heuristic analysis, real-time protection, and automated signature updates. As a pedagogical platform, it serves as a bridge between theory and practice—illustrating file system operations, cryptographic applications, and data-driven threat identification. Future development may expand the scanner into a more comprehensive framework incorporating multi-layered detection, cloud-based updates, and AI-based classification. Ultimately, the project emphasizes clarity and accessibility, making it a valuable resource for students, educators, and cybersecurity enthusiasts seeking practical insight into antivirus design principles and malware detection logic.